Implementation of Instructor Professional Program for Increasing Instructor Competency Improvement (Cave Rescue) Basarnas Education and Training Center - Sisilia Ayu Sulistyani (Proceeding International Conference on Religion, Science and Education, 2023)
Teaching staff or better known as instructors within the scope of the Education and Training Center are the frontlines who are the benchmark for success in developing employee competencies. Therefore, instructors need continuous competency development as public servants. Competency development is accommodated through a proficiency program tailored to training needs. On the other hand, competency development is also an ASN’s right as stipulated in Law No. 25 of 2014 concerning State Civil Apparatuses. The purpose of this study was to analyze the implementation of the instructor’s proficiency program in order to increase competence in the field of cave rescue which was carried out using a descriptive method through a qualitative approach referring to the Tyler model. The results of the program achievement analysis referred to the Tyler model explaining that the proficiency program for increasing the competence of instructors in the field of cave rescue can be achieved well, but continuous repetition is needed as a measure of the absorption of learning understanding. This is also evidenced by the increase in technical competency after completing the program.